Food and the Concept of Salvation: Questioning Javanese Ethics in Environmental Issues - Imamah, Fardan Mahmudatul (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2025)
Most studies refer to food as a symbol of salvation in Javanese beliefs. However, only some of these studies linked the interpretation of Javanese beliefs about the concept of salvation with values of environmental ethics. This research aims to uncover other interpretations of Javanese life ethics about environmental issues embedded in cultural rituals’ food symbols. The objects of this research are two traditions in Javanese society. First, Takir Plontang, ritual which is held by people of Junjung Village, Tulungagung Regency. Second, GrebegPancasila in Blitar City. The Javanese community organizes Takir Plontang Ritual at the beginning of the new year, Suro, by eating together at the village crossroads. As for Grebeg Pancasila, it is an annual activity of Blitar City to celebrate the birth of Pancasila every June 1 and this activity has five gunungan kirab festival as an expression of gratitude for the crops. The research used participant observation and interview methods to collect data. Unlike other Javanese ritual studies focusing on spiritual values in Javanese ceremonies which emphasize social cohesion, this study wishes to connect how far the concept of salvation symbolized through food in Javanese celebration ceremonies is linked to environmental ethics by balancing human and non-human relationships. The results showed that, in general, Javanese people connect Takir Plontang ritual as a gathering to pray for the salvation of their families and descendants. They believe that this ritual is a means to connect them with their ancestors and strengthen human inner power as a source of life balance. The imbalance between human inner power and the environment will cause disasters. As for the other ritual, people believe in seeking blessings from the crops in the five gunungan which have been prayed for in Bung Karno’s grave, has power beyond the world. People enthusiastically compete for part of the five gunungan as a form of gratitude for crops, respect, and blessings from God. Food symbolizes balance and salvation in rituals and festivals, highlighting nature as part of their lives and contributing to human welfare. However, nature is not valued as a subject/agency as the subject of ethics but as a medium and consequence in the relationship between people and their ancestors and spirits.